Analisis Perilaku Kebiasaan Membuang Sampah di Pantai Loang Baloq Kota Mataram - Fitria, Nazima; Aprilia S, Komang Ratna; Khumaira S, Baiq Fadya; Supardiono, Supardiono; Dujana, Lalu Muhammad Aby (Lembaga Pendidikan, Penelitian, dan Pengabdian Kamandanu, 2026)
This study aims to analyze the waste disposal behavior of visitors to Loang Baloq Beach, Mataram City, and the factors influencing it. This study used a quantitative descriptive approach involving 35 respondents selected through accidental sampling in December 2025. Data were collected through a closed-ended questionnaire using a Likert scale, field observations, and documentation, then analyzed descriptively through frequency calculations, percentages, and average values. The results showed that most respondents had a very good level of hygiene knowledge, but proactive behavior in maintaining cleanliness was still low. Basic behavior of disposing of waste in the proper place was high, while advanced behaviors such as picking up trash, bringing home recyclable waste, and reprimanding violators were still rare. This condition was supported by limited trash bin facilities, a lack of warning signs, and a lack of supervision at the study site. These findings indicate a gap between knowledge and practice of hygiene behavior in the Loang Baloq Beach area.